Kemampuan Menggunakan Ada Passompung ‘Konjungsi’ pada Karangan Narasi Bahasa Bugis Siswa Sekolah Menengah Pertama - Ade Shindy Arlinda; Syamsudduha Syamsudduha; Andi Fatimah Junus (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This research is a quantitative descriptive study aimed at describing students' ability to use coordinative and subordinative conjunctions in Buginese language narrative essays for class VII students. The object of this research was UPTD class students at SMPN Satap 9 Barru, while the research sample was class VII students. The data collection technique used in this study was a written test. The data analysis technique is, First, the criteria for using there are coordinative and subordinate conjunctions. Second, Changing the standard value of the raw score, Third, Determining the benchmark with a percentage. Based on the results of data analysis students were able to use the coordinative conjunction 'passompung' in their Buginese narrative essay compared to using the subordinating conjunction 'passompung'. Keywords: Capability There Passompung, Coordinating, Subordinating